Running economy and performance. High and low intensity efforts during training and warm-up. A bibliographic review - González-Mohino Mayoralas, F.; Jiménez Diaz, J. F.; Juárez Santos-Garcia, D.; Barragán Castellanos, R.; Yustres, I.; González-Ravé, J. M. (Archivos de medicina del deporte, 2018)
Interest in relation to running economy has increased such as determinant of running performance in scientific literature in trained long and middle distance runners and recreational runners. Trained runners are more efficient than untrained runners, meaning it is a "trainable" parameter. A key factor during endurance training is the intensity of corresponding effort, characterized by two endurance training methods such as interval and continuous training. In recreational runners, there is some controversy about which intensities are optimal in order to improve running economy, thus, periodized endurance training with a logical relationship between high and low-intensity training is recommended. We recommend the inclusion of 2-3 session per week of interval training, compensated with continuous training. Regarding to trained runners, interval training (at intensities close to VO2max) will be more important because of the need to be more economical at competitive intensities. Very high training intensities would not lead improvements in running economy due to it is not posible to accumulate enough training volumen during the training period. Conversely, the high-intensity efforts prior to competition (intensities above anaerobic threshold), during a warm-up protocol, increase the energy cost (reduce the running economy) and therefore, it is recommended a long transient phase (9-20 min) before to competition so as not to disturb the subsequent performance. An increase of scientific studies regarding the effects of high-intensity efforts during a warm-up protocol is needed in order to know the optimal intensities, flat or uphill ground, or the adequate recovery to improve the subsequent performance